2015
DOI: 10.3892/mco.2015.551
|View full text |Cite
|
Sign up to set email alerts
|

Preferentially examined sentinel nodes for sentinel node navigation surgery in gastric cancer

Abstract: Abstract. The intraoperative examination of the sentinel nodes (SNs) is crucial for correctly performing SN navigation surgery (SNNS). Frozen-section diagnosis is ordinarily used; however, when several SNs are being assessed in gastric cancer, which has numerous regional lymph nodes, it is difficult to examine them all correctly within the short duration of surgery. In the present study, we aimed to determine the SNs that should be preferentially examined during SNNS in gastric cancer. A total of 824 SNs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Furthermore, given that they rely on only 11 patients who were SN metastasis positive, the results of this study should be accepted with considerable caution. Yaguchi et al suggested that RI counting is a feasible approach for identifying metastatic SNs [30], and the results of the present study are similar to their results, which would support the novel findings of that group.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, given that they rely on only 11 patients who were SN metastasis positive, the results of this study should be accepted with considerable caution. Yaguchi et al suggested that RI counting is a feasible approach for identifying metastatic SNs [30], and the results of the present study are similar to their results, which would support the novel findings of that group.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, the sentinel node (SN) concept has been widely accepted, and SN navigation surgery (SNNS) is a standard surgical procedure for early-stage melanoma and breast cancer (1). However, the clinical application of SNNS for cT1 gastric cancer had been controversial, because of the complexity of the lymphatic flow compared to breast cancer and melanoma (2).…”
Section: Introductionmentioning
confidence: 99%